Optimalisasi Kesejahteraan Left-behind Children pada Keluarga Pekerja Migran di Pedesaan melalui Penguatan Sistem Keluarga Inti: Sebuah Perspektif dari Sisi Anak - Alfiasari; Sumarti, Titik; Sri Wahyuni, Ekawati; Rahmayani Johan, Irni (Sodality: Jurnal Sosiologi Pedesaan, 2022)
Children who are left by their parents who work outside the region or abroad as migrant workers will face various well-being problems. This requires a further study to explore the well-being of left-behind children of migrant workers' families in Indonesia, both circular migrant workers and international migrant workers. This study aimed to analyze left-behind children's subjective well-being condition and its relation to family-based social capital and social support that children of migrant worker families perceive. This study is expected to be an initial finding to direct further studies related to strengthening the nuclear family system for families of migrant workers who can optimize the left-behind children's well-being of families of migrant workers. This research was conducted in Juntinyuat, Limbangan, and Dadap Villages, Juntinyuat District, Indramayu Regency. The sampling technique used snowball sampling with samples of children aged 12-18 years from families of migrant workers, both circular and international. The total respondents were 120 children whose data were collected through a self-administered method. The study found that left-behind children whose mothers worked as international migrant workers were more vulnerable to their well-being than other left-behind children. The role of family-based social capital and social support as components in strengthening the nuclear family system of migrant worker families is discussed further in this article